2010
DOI: 10.1007/s12311-010-0203-8
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Olive Response to Passive Tactile and Visual Stimulation with Variable Interstimulus Intervals

Abstract: The unique anatomical and electrophysiological features of the inferior olive and its importance to cerebellar function have been recognized for decades. However, understanding the exact function of the inferior olive has been limited by the general lack of correlation between its neural activity and specific behavioral states. Electrophysiological studies in animals showed that the inferior olive response to sensory stimuli is generally invariant to stimulus properties but is enhanced by unexpected stimuli. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Our results highlight the specific functional role of several areas, including the putamen and caudate, the temporal cortex, and primarily the cerebellum, an area previously commonly associated with temporal tasks, although probably of an underspecified level of contribution [ 11 ]. Our finding of high activation in the cerebellum associated with increasing speed, and hence also with the difficulty of the task, is well in accordance with previous studies of subsecond spectrum retrospective temporal processing utilizing transcranial magnetic stimulation of the cerebellum [ 39 41 ] and imaging methods [ 25 , 42 46 ], and also with the hypothesis that this neural node acts as a timing system for brief intervals [ 47 ]. Even if reported as the most commonly engaged structure in retrospective subsecond temporal computing [ 5 ], the extent of the volume of activated cerebellar tissue and the dominance of the cerebellar cluster in the current study far exceeds the volumes and the rank among the other neural nodes reported in retrospective timing tasks [ 3 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our results highlight the specific functional role of several areas, including the putamen and caudate, the temporal cortex, and primarily the cerebellum, an area previously commonly associated with temporal tasks, although probably of an underspecified level of contribution [ 11 ]. Our finding of high activation in the cerebellum associated with increasing speed, and hence also with the difficulty of the task, is well in accordance with previous studies of subsecond spectrum retrospective temporal processing utilizing transcranial magnetic stimulation of the cerebellum [ 39 41 ] and imaging methods [ 25 , 42 46 ], and also with the hypothesis that this neural node acts as a timing system for brief intervals [ 47 ]. Even if reported as the most commonly engaged structure in retrospective subsecond temporal computing [ 5 ], the extent of the volume of activated cerebellar tissue and the dominance of the cerebellar cluster in the current study far exceeds the volumes and the rank among the other neural nodes reported in retrospective timing tasks [ 3 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, it was markedly larger following a violation, consistent with the idea that the cerebellum was sensitive to temporal prediction violations. Further support for this idea comes from fMRI work showing larger cerebellar activation to visual stimuli with unpredictable timing (e.g., [ 161 ]) as well as a study in which an early ERP signal to deviant auditory stimuli was found to be abnormal in patients with cerebellar degeneration [ 162 ].…”
Section: Sensory Processing and The Cerebellum: Timing (Rb Ivry)mentioning
confidence: 99%
“…Other studies revealed that the IO is involved in the cognitive property of perception of temporal complex rhythmic stimuli (Xu et al, 2006; Liu et al, 2008; Wu et al, 2010). The impact of mefloquine on the IO and on the olivocerebellar dependent behaviors has never been investigated in humans.…”
Section: Introductionmentioning
confidence: 97%